Characterization of ethylene–vinyl acetate (EVA)/modified starch expanded compounds for outsole material - Dwi Wahini Nurhajati; Umi Reza Lestari; Gunawan Priambodo (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2021)
The use of non-biodegradable material in shoe components has negative impacts on environmental sustainability when disposed into landfills due to poor biodegradability. This study prepared ethylene–vinyl acetate (EVA)/modified starch expanded compounds as outsole material to overcome environmental pollution. This research aimed to investigate the effects of EVA/modified starch ratio on the properties of the compound. Ethylene-vinyl acetate (EVA) copolymer was blended with a modified cassava starch in various amounts (10-50 phr) using a two-roll mill. Effect of modified starch content was characterized its tensile strength, elongation at break, tearing strength, 50% permanent set, density, abrasion resistance, flex resistance, biodegradability, and morphology. The optimum value of tensile strength (61.33 kg/cm²), elongation at break (895%), and tear strength (16.62 N/mm) were obtained for samples containing 20 phr modified starch. The EVA compound containing 30 phr of starch showed the optimum 50% permanent set (4.85%) and the highest abrasion resistance with the smallest volume loss of 439.99 mm³. The addition of modified starch up to 50 phr provided good flexural resistance to 150000 number of cycles. The morphology image showed that distribution of modified starch particles was not homogeneously dispersed in the EVA/modified starch expanded compound. Incorporation of modified starch in EVA compound was improving its biodegradability.